2011
DOI: 10.1080/08870440903440699
|View full text |Cite
|
Sign up to set email alerts
|

That which doesn’t kill us can make us stronger (and more satisfied with life): The contribution of personal and social changes to well-being after acquired brain injury

Abstract: This study examined the roles of personal and social changes on the relationship between injury severity and life satisfaction among individuals with acquired brain injury (ABI). Personal change (i.e. having developed a survivor identity, identity strength), social changes (i.e. improved social relationships, support from services), injury severity (i.e. length of time in coma) and well-being (i.e. life satisfaction) were assessed in a sample of 630 individuals with ABIs. A counterintuitive positive relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 36 publications
4
83
1
1
Order By: Relevance
“…Injury severity and its influence on wellbeing or life satisfaction has been the subject of much discussion over the years, with studies often showing results contrary to expectations (Albrecht & Devlieger, 1999;Jones et al, 2011;Post & Noreau, 2005). Many of these studies have focussed on more serious trauma, such as spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injury severity and its influence on wellbeing or life satisfaction has been the subject of much discussion over the years, with studies often showing results contrary to expectations (Albrecht & Devlieger, 1999;Jones et al, 2011;Post & Noreau, 2005). Many of these studies have focussed on more serious trauma, such as spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, many studies have concentrated on people with spinal cord or traumatic brain injury. Interestingly, results from many of these studies have reported better life satisfaction and quality of life than was expected (Albrecht & Devlieger, 1999;Dijkers, 2004;Jones et al, 2011;Post & Noreau, 2005). Some explanations for this propose a "response shift" (Dijkers, 2004) or adaptation process (Menzel, Dolan, Richardson, & Olsen, 2002), whereby people adapt to challenges presented to them by changing their internal standard of expectations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 At present, the postacute coordination of rehabilitation arrangements largely falls to consumers and their families. 18 The task of mobilizing complex support systems can be impossible for people with brain injury, who are vulnerable to reduced social networks 10,12 and who may have a compromised ability to form and maintain social linkages with others.…”
Section: Whole-of-system Approachmentioning
confidence: 99%
“…At this time, it is not uncommon for significant social and behavioral challenges to emerge including impulsiveness, sexual disinhibition, aggression, diminished insight, and poor judgment. [8][9][10] These behaviors complicate the process of regaining employment, re-establishing financial independence, and maintaining relationships, resulting in social isolation, unemployment, poverty, poor health, criminal behavior, and family breakdown. Ironically, as reported elsewhere, 2 there is a long-term cost benefit of providing early psychosocial intervention to people with brain injury.…”
Section: (P101)mentioning
confidence: 99%